Cryptococcal meningitis after transnasal transsphenoidal pituitary microsurgery of ACTH-secreting pituitary adenoma: A case report. Issue 28 (July 2017) - Liu, Yang; Feng, Ming; Yao, Yong; Deng, Kan; Bao, Xinjie; Liu, Xiaohai; Wang, Renzhi
Abstract: Rationale: Microbial infection should be regarded in the differential diagnosis of neurosurgical complications after transnasal transsphenoidal pituitary microsurgery, albeit cryptococcal meningitis is rare. This article will discuss the risk factors of cryptococcal meningitis in patients underwent transnasal transsphenoidal pituitary microsurgery, and summary the potential origins of infection. Patient concerns and diagnosis: Here, we report a case of 37-year-old male who had cryptococcal meningitis after transnasal transsphenoidal pituitary microsurgery of a relapsing ACTH-secreting pituitary adenoma. Intervention: Standard therapy for Cryptococcus neoformans (fluconazole [400 mg per day] and flucytosine) was administered and followed by maintenance dose. Outcomes: The patient had been on treatment for one and a half years during follow-up and reported neurologically well with repeated negative cerebrospinal fluid (CSF) culture until sudden death of heart arrest. Main lessons to learn: C neoformans can be a possible cause of meningitis in immunocompetent patients after transnasal transsphenoidal pituitary microsurgery. Risk factors, such as pre-existed pulmonary infection and Cushing-associated hypercortisolemia, should be stressed. Promising preventive measures may include preoperative routine sputum smear and India-ink stain for screening, preoperative treatment of cryptococcal pneumonia, postoperative antibiotic management, and a more secure skull base reconstruction. Radiation and pharmaceutical treatment may be alternative for recurrent Cushing disease.